Nitrogen Doping Improves the Immobilization and Catalytic Effects of Co9S8 in Li‐S Batteries. (21st June 2020) - Liu, Yuping; Ma, Shuangying; Liu, Lifeng; Koch, Julian; Rosebrock, Marina; Li, Taoran; Bettels, Frederik; He, Tao; Pfnür, Herbert; Bigall, Nadja C.; Feldhoff, Armin; Ding, Fei; et al.
Abstract: Several critical issues, such as the shuttling effect and the sluggish reaction kinetics, exist in the design of high‐performance lithium–sulfur (Li‐S) batteries. Here, it is reported that nitrogen doping can simultaneously and significantly improve both the immobilization and catalyzation effects of Co9 S8 nanoparticles in Li‐S batteries. Combining the theoretical calculations with experimental investigations, it is revealed that nitrogen atoms can increase the binding energies between LiPSs and Co9 S8, and as well as alleviate the sluggish kinetics of Li‐S chemistry in the Li2 S6 cathode. The same effects are also observed when adding N‐Co9 S8 nanoparticles into the commercial Li2 S cathode (which has various intrinsic advantages, but unfortunately a high overpotential). A remarkable improvement in the battery performances in both cases is observed. The work brings heteroatom‐doped Co9 S8 to the attention of designing high‐performance Li‐S batteries. A fundamental understanding of the inhibition of LiPSs shuttle and the catalytic effect of Li2 S in the newly developed system may encourage more effort along this interesting direction. Abstract : Nitrogen doping simultaneously and significantly improving the immobilization and catalyzation of the polysulfides by Co9 S8 nanoparticles is reported. These N‐Co9 S8 nanoparticles show effective suppression of the shuttling behavior, and as well as a significant acceleration of redox reaction kinetic in Li‐S batteries, especially the catalytic effect for Li2 S.